Faktor-Faktor Yang Mempengaruhi Corporate Bond Underpricing - Irma Suryani Indra; Elvira Luthan; Amy Fontanella (Jurnal Ecogen, 2022)
This study aims to determine what factors influence corporate bond underpricing in companies listed on the IDX in 2017-2021. This research is a quantitative study, using secondary data collected through the official website of the IDX and the company's website. The population used in this study is all companies issuing bonds in 2017-2021 using a purposive sampling technique for the sample selection method. This study uses multiple linear analysis, which in this study shows that underwriter reputation has a significant effect on corporate bond underpricing. Meanwhile, Accrual Quality Family Involvement, firm age and profitability have no significant effect on corporate bond underpricing.